Design and testing of a deflector integrated cross axis wind turbine / Wan Khairul Muzammil Abdul Rahim - Wan Khairul Muzammil, Abdul Rahim (2018)

(untitled)
The consequences of global modernisation have increased the demand for energy, which led to the interests for alternative energies, such as wind energy. However, in unfavourable wind conditions, factors such as low wind speed, high turbulence and wind direction variations can reduce the performance of horizontal axis wind turbines (HAWT). Certain vertical axis wind turbine (VAWT) design perform well under these harsh operating conditions, but these wind rotors typically have low power coefficients. To overcome these problems, a novel design of deflector integrated cross axis wind turbine (CAWT) is proposed. This is achieved through improved design of the wind rotor via harnessing wind energy from both the horizontal and vertical components of the oncoming wind by using the deflector. Experiments using deflectors to guide the oncoming airflow upward were designed to test the CAWT performance with various inclination angles. Different horizontal blade pitch angles CAWT were also fabricated to ascertain their characteristics. A conventional Darrieus VAWT was tested under the same experimental conditions for benchmarking purposes. It was found that the CAWT’s peak power coefficients, CP integrated with the 45° deflector were increased significantly by 103, 154, 172 and 175% at tip speed ratios, TSRs of 0.70, 0.87, 0.92 and 0.93 for horizontal blade pitch angles, β of 0°, 5°, 10° and 15°, respectively. The same configuration CAWTs recorded the highest improvement of rotor rotational speeds amongst the other configurations with 363.1 rpm (78.0%), 433.1 rpm (112.3%), 412.5 rpm (102.2%) and 347.5 rpm (70.3%), respectively. Several unique characteristics of the CAWT and VAWT were observed. Firstly, the CAWTs in bare configurations produced higher power output compared to the VAWT, except for the 15° pitch angle CAWT. Then, the use of deflectors enhanced the performance of the CAWTs. However, the performance of the VAWT was observed to decline by 19% after the deflectors were integrated. Lastly, the data from the experiments showed that the torque coefficient, CQ of the 15° pitch angle CAWT integrated with the deflector is 87% higher than the VAWT, suggesting that the CAWT has a better ability to self-start in low wind speed and skewed wind conditions. A semi-empirical approach was also developed to analyse the performance of the CAWT. The aerodynamic behaviour of the CAWT was determined by combining the blade element momentum (BEM) and double multiple stream tube (DMST) models. The approach emphasised on the blade aerodynamics, inflow distribution, and torque distribution around the rotor. Moreover, the approach showed notable agreement between the experimental and analytical results. Finally, the feasibility of wind augmenting device as a compact on-site renewable energy generation system was explored with the omni-direction-guide-vane (ODGV) and a VAWT. The ODGV acts as a wind concentrator, whereby the wind energy output was increased by 3.48 times in comparison to a conventional rotor. By integrating the ODGV with a VAWT, the annual operating hours and energy generated from the system in Sepang and Subang can be increased by 41% and 438%, and 25% and 305%, respectively.